2018
DOI: 10.1007/s11739-018-1989-5
|View full text |Cite
|
Sign up to set email alerts
|

Detecting delirium in elderly medical emergency patients: validation and subsequent modification of the German Nursing Delirium Screening Scale

Abstract: Detecting delirium in elderly emergency patients is critical to their outcome. The Nursing Delirium Screening Scale (Nu-DESC) is a short, feasible instrument that allows nurses to systematically screen for delirium. This is the first study to validate the Nu-DESC in a German emergency department (ED). The Nu-DESC was implemented in a high-volume, interdisciplinary German ED. A consecutively recruited sample of medical patients aged ≥ 70 years was screened by assigned nurses who performed the Nu-DESC as part of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 31 publications
0
8
0
1
Order By: Relevance
“…Another exclusion was due to insufficient data to derive a 2 × 2 table for evaluating Nu‐DESC test accuracy (Poikajarvi et al, 2017) and the other one used a modified, not an original, version of the Nu‐DESC (Kim, Kim, Kim, Yoo, & Park, 2012). Finally, we identified 11 articles that met our eligibility criteria, which were systematically reviewed and used in our meta‐analysis for DTA of the Nu‐DESC (Brich et al., 2018; Gaudreau et al., 2005; Hargrave et al., 2017; Heinrich et al., 2019; Leung et al., 2008; Lingehall et al., 2012; Luetz et al., 2010; Neufeld et al., 2013; Radtke et al., 2008, 2010; Saller et al., 2019). None of the 11 articles was from unpublished literature.…”
Section: The Reviewmentioning
confidence: 99%
“…Another exclusion was due to insufficient data to derive a 2 × 2 table for evaluating Nu‐DESC test accuracy (Poikajarvi et al, 2017) and the other one used a modified, not an original, version of the Nu‐DESC (Kim, Kim, Kim, Yoo, & Park, 2012). Finally, we identified 11 articles that met our eligibility criteria, which were systematically reviewed and used in our meta‐analysis for DTA of the Nu‐DESC (Brich et al., 2018; Gaudreau et al., 2005; Hargrave et al., 2017; Heinrich et al., 2019; Leung et al., 2008; Lingehall et al., 2012; Luetz et al., 2010; Neufeld et al., 2013; Radtke et al., 2008, 2010; Saller et al., 2019). None of the 11 articles was from unpublished literature.…”
Section: The Reviewmentioning
confidence: 99%
“…It showed that the evaluation of item 1 (disorientation) combined with two elements of the Mini-Mental State Examination (MMSE) indicates that asking the patient the day of the week and name of the unit where he or she is located increases sensitivity from 66 % to 77.8 %. This finding contrasts with the results obtained in the same study, where the disorientation item was not identified in 14 of 16 false positives cases (32). Although questions arise about the ability of Nu-DESC to detect all forms of delirium, it is necessary to add the capacity to discriminate between delirium and differential diagnosis; Spendale et al demonstrated it in a study of 101 patients hospitalized in different units where 79 % of positive cases had a history of cognitive impairment (33).…”
Section: Nu-desc and Its Use In Hospitalizationmentioning
confidence: 64%
“…For the caregivers the Family Confusion Assessment Method (FAM-CAM) will be used [ 31 ]. The five-item Nursing delirium screening scale (Nu-DESC) allows to rate attending nurses’ observations concerning disorientation, inappropriate behavior and communication, hallucinations and psychomotor retardation over a 24-h period [ 32 ]. For the interventional part of the study two easy to use screening instruments for delirium were added to the assessment battery: The bedside confusion scale (BCS) as a simple and short test for delirium that can be derived from 3D-CAM assessment and focuses on the items psychomotor disturbance and awareness [ 33 ].…”
Section: Methodsmentioning
confidence: 99%